Rapid generation of approximate optical spectra of dense cool plasmas - Heading, D; Machacek, A; Whitford, L; Varney, A; Wark, J; Lee, R; Stamm, R; Talin, B (1997)
In recent experiments uniform plasmas have been generated at high densities and low temperatures, (typically electron densities of 10(19) cm(-3) and T similar to 2 - 5 eV). Additionally, such plasmas are also produced during free laser ablation - a topic of relevance to the deposition of thin solid films. Standard methods used to diagnose plasmas are difficult to apply at these conditions, as there is significant overlap of the broad spectral lines from different elements and ion stages. It is therefore of interest to attempt to calculate the entire spectrum in the appropriate wavelength regime. For most elements, the number of individual spectral line profiles that have been calculated as a, function of density and temperature using the semi-classical method is very small, hindering such a synthesis of the full spectra. However, a technique for approximating line shapes simply and rapidly (the modified semi-empirical method) has previously been developed for individual lines. We utilise this method, coupled with an accurate database, to generate a large number of density dependent line profiles, and hence an approximation to the full spectrum. We evaluate the accuracy and utility of such an approach by comparison with the few extant semi-classical calculations. The method described facilitates the rapid generation of approximate spectra. It can also be used as a post processor to a hydrodynamic code to obtain both time dependent and time integrated spectra in the approximation that the laser-ablated plasma is both optically thin and in LTE. (C) 1997 Elsevier Science Ltd. All rights reserved.